Implementasi Pendidikan Islam Melalui Majelis Taklim dalam Membina Karakter Islami Masyarakat di Era Society 5.0: Studi Kualitatif di Kecamatan Sukra, Indramayu - Madropi Madropi; Burhanudin Burhanudin (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2026)
This study is motivated by the phenomenon of moral degradation and character education challenges amidst the technological disruption of the Society 5.0 era. Majelis Taklim, as a non-formal Islamic educational institution, plays a strategic role in fortifying and fostering the community's character. This study aims to describe the implementation of Islamic education, analyze the process of Islamic character building, and identify supporting and inhibiting factors in Sukra District, Indramayu Regency. Using a qualitative approach with a descriptive design, data were collected through participatory observation, in-depth interviews, and documentation across 8 Majelis Taklim in Sukra District. Data analysis utilized the Miles, Huberman, and Saldaña model. Data validity was tested through source triangulation, technique triangulation, and member checking. The results indicate that the implementation of Islamic education is carried out through routine recitations, Qur'anic literacy, exemplary role modeling (uswah hasanah), and socio-religious actions. The character building process occurs through value internalization via habituation, advice (mau'izhah), and personal approaches. The formed characters include religiosity, honesty, discipline, social care, and akhlakul karimah. The main supporting factors are the high socio-religious capital of the coastal-pantura community and the support of community leaders. However, challenges such as the hegemony of social media, low youth participation, and agrarian-fishermen work commitments become structural barriers. This study concludes that Majelis Taklim remains highly relevant as an agent of moral reproduction, but it demands innovative dakwah methods that are adaptive to the digital ecosystem.